"Unwanted" and "bad, " but not "sexual": Non-labelling of sexual harassment by Sri Lankan working women. Issue 5 (1st August 2016) - Adikaram, Arosha S.
Abstract : Purpose: – As prior research has indicated, women who experience behaviors that fall under the accepted definitions of sexual harassment, do not label, acknowledge, or claim these behaviors as such. The purpose of this paper is to explore an alternative explanation for this non-labeling by arguing that apprehension in expressing sexuality, stemming from apparent subjugation of sex and sexuality by society, posited in a culturally value laden backdrop, leads to Sri Lankan women not labeling or acknowledging sexual harassment. Design/methodology/approach: – Employing grounded theory, in-depth, one-on-one interviews were conducted with 40 working women. Findings: – It was revealed that social construction of gender and sexuality in Sri Lankan society, with its instilled moralistic beliefs and norms such as respectability, sexual innocence, chastity, and purity among women, suppress and govern their sexuality in the workplace. The resultant self-surveillance and self-discipline lead to women evading expressing and using vocabulary denoting sexuality – including the term "sexual harassment" – mainly for fear of social censorship, self-blame, and victim blame. Practical implications: – The study shows how policies and procedures of sexual harassment must heed the gendered everyday realities of women in workplaces and questions the capacity and utilization of these laws and policies that employ the label "sexual" in addressing the issue. Originality/value: – This paper advances knowledge on sexual harassment by providing new insights on how cultural values and norms leading to social construction of gender and sexuality play an important role in non-labeling of sexual harassment. Moving further, this paper illustrates how Foucault's treatise of "sexuality and power, " and "social construction of reality" can be employed to theorize non-labeling.